Menari Bersama Marya - I Komang Tri Ray Dewantara; Ni Wayan Suartini (Jurnal IGEL : Journal Of Dance, 2025)
ABSTRACT “MENARI BERSAMA MARYA” I Komang Tri Ray Dewantara mangtriray@gmail.com This article discusses the creation of a dance work based on research through an archival dance approach titled "Dancing with Marya." The creation of the "Dancing with Marya" work was motivated by the choreographer's artistic practice of examining the archives of the Kebyar Duduk dance to question the distance and changes between the Kebyar Duduk movements recorded in the archives and those performed and taught today. "Dancing with Marya" employs a methodology or creative framework developed collaboratively with Teater Garasi, which follows a linear process encompassing several stages: locating the questions, source works, improvisation, codification, composition, and presentation. This project enables the choreographer to revisit the shifts in the construction of the dance and the dancer's body in Kebyar Duduk from its initial creation to its current form, through an exploration of the genealogy/history of the dance and a physiological identification of I Ketut Marya's body. By observing Marya from the perspective of Kebyar Duduk dancers today, this project explores the possibilities offered by the dance archive while acknowledging the limitations of archives in fully recreating the bodily and dance events of the past, due to the ephemeral nature of dance. The performance is presented in a square space, creating an intimate distance between the dancer and the audience, with visual projections of the archival materials serving as artistic support. Keywords: archive, Kebyar Duduk, I Ketut Marya, genealogy, physiological, ephemeral